Ontwikkeling Van Omvattende Gesondheidsdienste in DieSelfregerende Swart Gebiede In Suider-Afrika - J.P. Roux (AOSIS, 1978)
In the development of health services in the selfgoverning Black territories of South Africa cognisance was taken of the modern holistic concept of health care delivery. The comprehensive hospital-centric health services in these territories have been supplemented by the introduction of community health centres with a broad spectrum of available services. These community health centres make provision for the basic health needs of the different communities and stimulate community participation - a fundamental requirement for community development. Training facilities for nurses fulfil modern requirements but should be adapted to the health needs of developing communities. Conventional curative services are unlikely to meet the basic health needs of all people. The emphasis should be on primary health care - a concept embracing health and welfare in its entirety and not restricted to the provision of medical care or personal health services. Community health development is essentially a social process that should start off with the acceptance of the social function of health and should ensure that health technology is developed and applied in harmony with this social function.